Eksperimentasi Model Pembelajaran Student Facilitator and Explaining (SFE) terhadap Hasil Belajar ditinjau dari Kecerdasan Linguistik - Widyawati, Santi (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to determine: (1) Which gives higher learning outcomes between the Student Facilitator and Explaining (SFE) learning model with the conventional learning model on the subject matter of exponent of class X Semester odds SMA N 1 Seputih Surabaya academic year 2016/2017, (2) Which gives higher learning outcomes between students with high, medium, or low linguistic intelligence on the subject matter of exponents of class X Odd Semester SMA N 1 Seputih Surabaya academic year 2016/2017 (3) Is there an interaction between the Student Facilitator learning model And Explaining (SFE) and linguistic intelligence on students' mathematics learning outcomes of the subject matter of exponents of class X Semester odd in SMA N 1 Seputih Surabaya in academic year 2016/2017. This research is a comparative causal research with factorial design 3 3. The population of this research is all students of class X SMA Negeri 1 Seputih Surabaya, Central Lampung. Sampling was done by cluster random sampling. The sample of this research are students of class X.1 and X.2. The conclusion of this research is: (1) There is no difference of learning result of student mathematics between the SFE model with a conventional model in grade X student SMA N 1 Seputih Surabaya. (2) There is no difference of learning result of student mathematics observed from the linguistic intelligence of class X student SMA N 1 Seputih Surabaya. (3) There is no interaction between SFE learning model and linguistic intelligence of grade X students SMA N 1 Seputih Surabaya.